2005
DOI: 10.1128/iai.73.8.4895-4904.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofHelicobacter pyloriVirulence Gene Expression In Vitro and in the Rhesus Macaque

Abstract: We used a quantitative real-time reverse transcriptase PCR assay to measure the transcript abundance of 46 known and putative Helicobacter pylori virulence genes, including 24 genes on the Cag pathogenicity island. The expression profile of H. pylori cells grown in vitro was also compared to expression in vivo after experimental infection of rhesus macaques. Transcript abundance in vitro (mid-log phase) ranged from about 0.004 (feoB and hpaA) to 20 (ureAB, napA, and cag25) copies/cell. Expression of most genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
6
38
0
1
Order By: Relevance
“…2). Biopsies were taken under anaesthesia after an overnight fast 1 week and 1, 2 and 6 months postorogastric H. pylori infection 16 . We sequenced the genome of strain J166 (1,650,561 bp) on a Roche 454-Titanium FLX sequencer, and the genomes of 12 J166 macaque output (J166 output ) strains, three individual bacterial strains cultivated from each of the four biopsies on an Illumina MiSeq to an average coverage of  200.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Biopsies were taken under anaesthesia after an overnight fast 1 week and 1, 2 and 6 months postorogastric H. pylori infection 16 . We sequenced the genome of strain J166 (1,650,561 bp) on a Roche 454-Titanium FLX sequencer, and the genomes of 12 J166 macaque output (J166 output ) strains, three individual bacterial strains cultivated from each of the four biopsies on an Illumina MiSeq to an average coverage of  200.…”
Section: Resultsmentioning
confidence: 99%
“…in this re-infection study and to 7.5 Â 10 8 c.f.u. in the macaque infection 16 , a cag PAI-negative strain and infection of an immunologically naive host 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that cagA was expressed at high levels during the entire time course of infection. Interestingly, some cag genes, such as cagY, were more highly expressed at 1 week post-infection compared with later time points, whereas expression of others, such as cagC, increased between 2 and 3 months and then fell by 4-6 months post-challenge (Boonjakuakul et al, 2005). Thus, data obtained from these independent animal model systems indicate an important role for CagA and other products of the cag pathogenicity island in the development of H. pylori-induced disease, particularly gastric cancer.…”
Section: Disease Models and Mechanisms 51mentioning
confidence: 99%
“…One study used H. pylori-infected Rhesus monkeys to examine expression of genes within the cag island by quantitative real-time reverse transcriptase PCR (Boonjakuakul et al, 2005). These data indicated that cagA was expressed at high levels during the entire time course of infection.…”
Section: Disease Models and Mechanisms 51mentioning
confidence: 99%